Australian painters of the twentieth century - Pearce, Barry; Klepac, Lou, 1936- (Sydney : Beagle Press, 2000)
This volume (first of a series of three) is devoted to the achievements of Australian painters of the twentieth century, and features the work of nineteen artists, including Dobell, Nolan, Boyd, Cossington-Smith, Whiteley, Olsen, Drysdale and others. Each artist is accorded 12 pages of reproductions and an accompanying essay.
Margaret Preston -- Ian Fairweather -- Grace Cossington Smith -- Godfrey Miller -- Lloyd Rees -- William Dobell -- Russell Drysdale -- Albert Tucker -- Donald Friend -- James Gleeson -- Sidney Nolan -- Arthur Boyd -- John Brack -- Jeffrey Smart -- Fred Williams -- John Olsen -- William Robinson -- Colin Lanceley -- Brett Whiteley.
Includes bibliography: p. 249-250.
Keywords: Art, Australian; Art, Modern -- 20th century; Painters -- Australia -- 20th century